Scandinavia in the age of Vikings - Jón Viðar Sigurðsson, 1958- (Cornell University Press, 2021)
"For the reader taking their first steps into the fascinating history of the Vikings in Scandinavia, this book focuses on Viking activities within Scandinavia--not on their exploits abroad--and on some key aspects in Scandinavia's formation during the Viking Age: politics, social networks, conspicuous consumption, warrior mentality, social stratification, women's roles, religion, farms, and power centers"--